An O-methylflavone from Artemisia afra kills non-replicating hypoxic Mycobacterium tuberculosis - Kellogg, Joshua J. (2024)
Ethnopharmacological relevance: African wormwood (Artemisia afra Jacq. ex Willd.) has been used traditionally in southern Africa to treat illnesses causing fever and was recently shown to possess anti-tuberculosis activity. As tuberculosis is an endemic cause of fever in southern Africa, this suggests that the anti-tubercular activity of A. afra may have contributed to its traditional medicinal use. Aim of the study: Tuberculosis, caused by Mycobacterium tuberculosis (Mtb), is a deadly and debilitating disease globally affecting millions annually. Emerging drug-resistant Mtb strains endanger the efficacy of the current therapies employed to treat tuberculosis; therefore, there is an urgent need to develop novel drugs to combat this disease. Given the reported activity of A. afra against Mtb, we sought to determine the mechanisms by which A. afra inhibits and kills this bacterium. Materials and methods: We used transcriptomics to investigate the impact of Artemisia spp. extracts on Mtb physiology. We then used chromatographic fractionation and biochemometric analyses to identify a bioactive fractions of A. afra extracts and identify an active compound. Results: Transcriptomic analysis revealed that A. afra exerts different effects on Mtb compared to A. annua or artemisinin, suggesting that A. afra possesses other phytochemicals with unique modes of action. A biochemometric study of A. afra resulted in the isolation of an O-methylflavone (1), 5-hydroxy-7-methoxy-2-(4- methoxyphenyl)chromen-4-one, which displayed considerable activity against Mtb strain mc 2 6230 in both log phase growth and metabolically downshifted hypoxic cultures. Conclusions: The present study demonstrated that an O-methylflavone constituent of Artemisia afra explains part of the activity of this plant against Mtb. This result contributes to a mechanistic understanding of the reported anti-tubercular activity of A. afra and highlights the need for further study of this traditional medicinal plant and its active compounds.